Big Data Analytics: An Innovative approach to adopt in emerging Sectors - Khamaru, Ananda (International Journal of Computer Sciences and Engineering, 2025)
In digital universe emerging trends of new technologies in different sectors are dramatically generating large amount of varieties [e.g.-structured and unstructured] of data every day. The low cost of memory is the reason to populate massive amount of data sets and it is too much heterogeneous to get a particular information is very troublesome. Day to day gathering of typical data makes a large complex datasets is called Big Data, which is difficult to capture and manage by conventional data processing system. The large complex datasets are stored among thousands of servers and Big Data technologies easily acquire and process those datasets. These technologies used in all sectors with big challenge to get better decision, quality assurance, risk management, etc. Adoption of big data technologies is opportunities to get the hidden pattern by acquired and analyzed a large scale, flexible, fault tolerance, and real time data which are resided in distributed files.